Mechanisms of recurrent regurgitation after transapical off-pump mitral valve repair with neochord implantation. (25th February 2019) - Colli, Andrea; Besola, Laura; Bizzotto, Eleonora; Fiocco, Alessandro; Denas, Gentian; Bellu, Roberto; Pradegan, Nicola; Nadali, Matteo; Gregio, Alessandro; Pittarello, Demetrio; Gerosa, Gino
Abstract: OBJECTIVES: The aim of this study was to describe possible mechanisms of recurrent mitral regurgitation (MR) in patients who have been treated with the NeoChord procedure. METHODS: Patients presenting with recurrent severe or moderate MR were categorized as Not Expected Surgical-Like Result (NESLR)-Redo and NESLR-MR2 [NESLR reintervention or moderate MR (2+), respectively]. NESLR patients were stratified by onset (intraoperative, perioperative 24 h–30 days, or early 30 days to follow-up), by MR jet direction (central or eccentric) and by jet orientation (anterior or posterior). Specific mechanisms of NESLR were analysed. RESULTS: Fifty-two patients were identified with 13 (25%) categorized as NESLR-Redo, and 39 (75%) as NESLR-MR2. NESLR-Redo patient stratification included: intraoperative = 2 patients (1.2%), both eccentric anteriorly directed jets; perioperative = 7 patients (4.2%), all eccentric with 3 anteriorly and 4 posteriorly directed jets; and early = 4 patients (2.4%), 1 central, 3 eccentric, 2 posteriorly and 1 anteriorly directed jets. NESLR-MR2 patient stratification included: perioperative = 2 patients (5.1%), both eccentric, 1 anteriorly and 1 posteriorly directed jets; and early = 37 patients (94.9%), 4 central, 33 eccentric, 22 anteriorly and 11 posteriorly directed jets. Possible mechanisms of recurrent MR were identified as: patient selection (17.3%), technical issues (28.8%), progression of baseline disease (15.4%), left ventricle reverse remodelling (1.9%), excessive over-tensioning (35.8%) and PML curling (30.8%). CONCLUSIONS: The mechanisms of recurrent MR after the NeoChord procedure can be determined. Understanding recurrent MR mechanisms has led to improvements in procedural standardization and ad hoc prevention strategies that have been widely adopted since our initial clinical experience.